2022
DOI: 10.1038/s41598-022-09936-w
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal [18]UCB-H/[18F]FDG imaging depicts complex patterns of structural and functional neuroplasticity following bilateral vestibular loss in the rat

Abstract: Neuronal lesions trigger mechanisms of structural and functional neuroplasticity, which can support recovery. However, the temporal and spatial appearance of structure–function changes and their interrelation remain unclear. The current study aimed to directly compare serial whole-brain in vivo measurements of functional plasticity (by [18F]FDG-PET) and structural synaptic plasticity (by [18F]UCB-H-PET) before and after bilateral labyrinthectomy in rats and investigate the effect of locomotor training. Complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
1
4
0
Order By: Relevance
“…As reported previously [30], chemical BL resulted in an acute decrease of neuronal activity within brainstem-cerebellar networks encompassing primary and secondary processing hubs (e.g., vestibular nuclei, inferior colliculus) of sensory cues from peripheral vestibular and auditory afferents. Decreased regional neuronal activity in brainstem-cerebellar networks only partially recovered during the studied period of 60 days post-BL.…”
Section: Impact Of Bilateral Labyrinthectomy and Post-surgery Recover...supporting
confidence: 78%
See 2 more Smart Citations
“…As reported previously [30], chemical BL resulted in an acute decrease of neuronal activity within brainstem-cerebellar networks encompassing primary and secondary processing hubs (e.g., vestibular nuclei, inferior colliculus) of sensory cues from peripheral vestibular and auditory afferents. Decreased regional neuronal activity in brainstem-cerebellar networks only partially recovered during the studied period of 60 days post-BL.…”
Section: Impact Of Bilateral Labyrinthectomy and Post-surgery Recover...supporting
confidence: 78%
“…In all rodents, a chemical BL was performed by transtympanic injection of bupivacaine and parsenic acid. On days 1,3,6,7,15,21,30,45, and 60 post-BL, low-intensity vestibular noise stimulation (nGVS at 0.2mA; N=8 animals) or sham stimulation (nGVS at 0mA; N=9 animals) was administered. Regional brain activation patterns and locomotion performance were assessed before BL and repetitively until day 60 post-BL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thalamus is an integrative center for multisensory inputs (vestibular, motor, and visual) and recent evidence suggests cerebellar projections from all three cerebellar nuclei reach most thalamic nuclei [ 39 ]. The rat thalamus has been shown to experience adaptive plasticity to bilateral labyrinthine loss [ 40 ]. While the cerebellum has the most CGRP binding sites in the brain and CGRP loss may significantly impact cerebellar activity, multisensory compensation mediated by the thalamus may result in recalibrated networks that can explain the modest rotarod improvements in the αCGRP -KO as they age.…”
Section: Discussionmentioning
confidence: 99%
“…In a bilateral chemical labyrinthectomy rat model, hippocampal glucose metabolism decreased on both sides from days 1–60 post lesion [ 24 ▪ ]. In vivo synaptic density imaging depicted no major synaptic loss in the hippocampus during this time period [ 41 ▪ ]. This finding is in accordance to older in vitro studies, which indicated no major synaptic loss in the hippocampus following bilateral vestibular deafferentation, but only a minor change in dendritic structure [ 42 ].…”
Section: Pathophysiology Of Spatial Navigation Disorders In Vestibulo...mentioning
confidence: 99%